Potts Shunt in Children With Familial Primary Pulmonary Hypertension: A Case Report and Brief Literature Review - Yazdan Ghandi; Ali Arjmand Shabestari; Mahya Mobinikhaledi (Mazandaran University of Medical Sciences, 2021)
Introduction: The primary concern about Familial Pulmonary Arterial Hypertension (FPAH) is the development of right heart failure, which ultimately leads to sudden death. Despite recent advances in pharmacological therapy, the mortality rate in children is still high, emphasizing the importance of novel treatments. Moreover, there is still no definitive treatment for children with severe pulmonary hypertension. The consequences of right heart failure led to the proposal of a surgical approach, the Potts shunt, to decompress the right ventricle, providing shunting of deoxygenated blood to lower extremities and improving overall cardiac output. This surgical technique creates an anastomosis between the left pulmonary artery and the descending aorta, providing a palliative treatment to off-load the right ventricle. Case Presentation: We report an 11-year-old girl with familial pulmonary arterial hypertension and right ventricular failure who benefited from a Potts shunt with good mid-term results. The patient was diagnosed at the age of 5 when she had a history of fainting and persistent syncope. The patient was under medical treatment therapy with bosentan, sildenafil, acetylsalicylic acid, and warfarin for six years. The results of molecular genetic testing, which was confirmed with direct sequencing of the Bone Morphogenetic Protein Receptor Type 2 (BMPR2) gene, revealed a heterozygous pathogenic mutation. Since she was diagnosed with Pulmonary Arterial Hypertension (PAH), she lost her grandmother, an aunt, and father because of PAH. Her 14-year-old sister also had mutated the BMPR2 gene without developing FPAH. Conclusions: The Potts shunt provides an interventional step for palliation of patients with familial pulmonary hypertension and severe right heart failure refractory to medical treatment. It opens the door to the possibility of lung transplantation in the future. We did not see any complications within 6 years after placing the Potts shunt.